Reimagining Urban Public Spaces: A Study of Spatial Rights and Community Interaction in Jabal Al-Hussein, Jordan - Alkhreasat, Ayat; Suleiman, Sarinaz (Journal of Islamic Architecture, 2025)
The paramount determinant of open space's success lies in the harmonious fusion of its design and environmental context. Considering people's environmental experience is crucial for implementing user-friendly spatial planning. This can be achieved by acknowledging the concept of "The Right to the City", which has two aspects: the right of residents to occupy, use, and enjoy specific city public spaces; and the right of residents to participate in decision-making at various stages in the urban planning process. This paper focuses on the first point only. The paper’s hypothesis emerged from the lack of POS in the study area, so streets are a public space where the community interacts, and does different activities. This paper studies the interactions between the physical setting of streets and open spaces with users. It traces all possible social, religious, and physical activities to reveal the level of spatial justice through the concept of spatial rights includes five dimensions. It comes out with three alternatives based on the conception of public spaces associated with mosques that emerged from a careful analysis of the needs of the residents of the study area (part of the Jabal Al-Hussein neighborhood).